2022
DOI: 10.1038/s41598-022-05083-4
|View full text |Cite
|
Sign up to set email alerts
|

The major plant sphingolipid long chain base phytosphingosine inhibits growth of bacterial and fungal plant pathogens

Abstract: Sphingolipid long chain bases (LCBs) are building blocks of sphingolipids and can serve as signalling molecules, but also have antimicrobial activity and were effective in reducing growth of a range of human pathogens. In plants, LCBs are linked to cell death processes and the regulation of defence reactions against pathogens, but their role in directly influencing growth of plant-interacting microorganisms has received little attention. Therefore, we tested the major plant LCB phytosphingosine in in vitro tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
9
1
Order By: Relevance
“…In the control group, the relative contents of phytosphingosine, carnitine, and arachidonic acid were significantly increased ( Figure 7 E). This is consistent with the notion that plants produce these defense-related compounds upon biotic stress [ 76 , 77 , 78 ]. This finding may be explained by the fact that antifungal peptides can have an immediate effect on plant pathogens, while the CK group relies more on the antifungal substances produced by itself.…”
Section: Resultssupporting
confidence: 91%
“…In the control group, the relative contents of phytosphingosine, carnitine, and arachidonic acid were significantly increased ( Figure 7 E). This is consistent with the notion that plants produce these defense-related compounds upon biotic stress [ 76 , 77 , 78 ]. This finding may be explained by the fact that antifungal peptides can have an immediate effect on plant pathogens, while the CK group relies more on the antifungal substances produced by itself.…”
Section: Resultssupporting
confidence: 91%
“…We and others previously demonstrated that the co-infiltration of Pst AvrRpm1 and d18:0 or t18:0, respectively, does not induce an HR in contrast to what happens with an infiltration of an avirulent bacteria or LCB alone (Magnin-Robert et al ., 2015; Glenz et al ., 2022). Therefore, Pst expressing effectors other than AvrRpm1 were selected to elucidate whether the absence of visible HR was dependent on the effector.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro tests showed that this LCB does not have an antibacterial effect on Pst AvrRpm1 , Pst AvrB and Pst AvrPphB , similarly to results obtained with P. aeruginosa (Fischer et al ., 2012). t18:0 has been shown to inhibit Pst growth (Glenz et al ., 2022). However, the authors used a smaller bacterial concentration and LB medium to perform their tests.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipid occur in cellular membranes of all eukaryotes, but only a few bacterial genera have it in their cell membrane [ 86 88 ]. Sphingolipid shows antimicrobial activity against a range of gram-positive and gram-negative pathogenic bacteria including Pseudomonas aeruginosa and Escherichia coli [ 50 ]. In our study, T9 showed the highest level of phytosphingosin and lower abundance level of Tenacibaculum.…”
Section: Discussionmentioning
confidence: 99%